Simulation Assisted Lessons and Students Conceptual Understanding of Electricity Concepts in Both Demonstrative and Exploratory Classrooms (London Journal of Research In Humanities and Social Sciences, 2023)
The study explored the effects of the interactive Physics Education Technology (PhET) simulation on conceptual understanding of Senior High School students on electricity concepts. The study employed the pre-test post-test non-equivalent control group design. A sample size of sixty-three (63) students from two schools participated in this study. The experimental group (School A) consisted of 32 students, and the control group (School B) consisted of 31 students. Intact classes were used. The electricity concept achievement test (ECAT) was the instrument used for data collection. It was revealed from the study that there was an improvement in conceptual understanding of students on “knowledge and understanding” and “application of knowledge” on electricity concepts taught with the PhET simulation in both a demonstrative classroom and an exploratory classroom (computer laboratory). However, no significant difference was observed in students’ conceptual understanding for students who were taught electricity concepts in a demonstrative classroom and those who were taught in an exploratory computer laboratory. It is therefore recommended that the PhET simulation should be used in teaching electricity concepts in physics either in a demonstrative classroom or in an exploratory classroom.
Keywords: Electricity; demonstrative classroom; exploratory classroom; simulation assisted lessons; conceptual understanding.